Neuroscience: detection of systemic inflammation by the brain - Kamm, Gretel B.; Siemens, Jan (Current biology, 2022)
When confronted with illness, humans and animals undergo critical changes in their behavior and physiology. New research shows how neuronal circuits detect sickness and coordinate illness-specific responses.
Gesehen am 28.08.2022